Ball-flower like CoS/g-C3N4 heterojunction photocatalyst for efficient and selective reduction of CO2 to CH4. (March 2023) - Wang, Fangjun; Wu, Jiang; Chen, Shiyi; Duan, Lunbo
Abstract: The efficient and selective reduction of CO2 to hydrocarbon fuels via photocatalytic reaction is an ideal choice for alleviating environmental pollution and utilizing clean energy. Herein, the CoS/g-C3 N4 heterojunction materials with different CoS mass ratios (10 wt%, 20 wt%, 30 wt%, and 40 wt%) were successfully prepared by ultrasonic-mechanical mixing, and applied for photoreduction of carbon dioxide for the first time. The formed p - n -type heterojunction can effectively slow down the recombination of photogenerated electron-hole pairs. The CoS/g-C3 N4 composite exhibits excellent photocatalytic activity and stability for CO2 reduction under visible light. After 3-hour illumination, the maximum CH4 yield over the 20 wt% CoS/g-C3 N4 sample reaches 121.74 μmol/gcat, which was 21.06 times and 5.44 times that of g-C3 N4 and CoS monomers. Furthermore, the CO production is negligible compared to CH4, indicating the superior product selectivity of the composite catalyst. Such significant promotion can be attributed to the well-matched energy band in the p - n heterojunction and the derived internal electric field, which results in a facilitated transfer of photogenerated charges as well as an improved utilization of visible light. This work well demonstrates that constructing heterojunctions is effective way to ameliorate the photocatalytic reduction of CO2 . Graphical Abstract: ga1 Highlights: A perfect band matching and efficient internal charge transfer within the p-n junction. The CoS/g-C3 N4 samples exhibit superior activity in the efficient and selective reduction of CO2 . Efficient separation of photogenerated electron-hole pairs. The CO2 adsorption and conversion progress is well revealed in the photoreaction.